2018
DOI: 10.1007/s10086-018-1725-9
|View full text |Cite
|
Sign up to set email alerts
|

Within-stem variations in mechanical properties of Melia azedarach planted in northern Vietnam

Abstract: Within-stem variations in the mechanical properties of 17-19-year-old Melia azedarach planted in two sites in northern Vietnam were examined by destructive and nondestructive methods. Wood samples were collected from 10, 50, and 90% of the radial length from pith on both sides (North and South) at 0.3, 1.3, 3.3, 5.3, and 7.3 m heights above the ground. The mean values in whole trees of wood density (WD), modulus of rupture (MOR), modulus of elasticity (MOE), and dynamic modulus of elasticity (E d) at 12% moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
3
12
0
2
Order By: Relevance
“…The similar observation was also observed in within the stem of Melia azedarach, the radial position was a highly (p<0.001) significant source of variation in mechanical properties. MOR, MOE, and E d increased from pith to bark [15]. Modulus of elasticity is also shows the same trend.…”
Section: Bending Tests Were Undertaken On Testing Machine Assupporting
confidence: 63%
“…The similar observation was also observed in within the stem of Melia azedarach, the radial position was a highly (p<0.001) significant source of variation in mechanical properties. MOR, MOE, and E d increased from pith to bark [15]. Modulus of elasticity is also shows the same trend.…”
Section: Bending Tests Were Undertaken On Testing Machine Assupporting
confidence: 63%
“…Mechanical properties of M. azedarach wood were also reported by some researchers (Matsumura et al 2006, Venson et al 2008, Duong and Matsumura 2018b, Duong et al 2019 who suggested the possibility of using wood of M. azedarach as a new timber source. Within-tree variation of M. azedarach physical (Duong and Matsumura 2018a) and mechanical wood properties (Duong and Matsumura 2018b) have also been examined, and it was observed that wood beyond ring 7 from the pith displayed mature wood properties, i.e. comparatively long fibers, high specific gravity, and low microfibril angle (MFA) in the S 2 layer of the cell wall (Duong et al 2017).…”
Section: Introductionsupporting
confidence: 62%
“…There are some reports on M. azedarach wood properties with general agreement that wood of M. azedarach has a medium specific gravity (SG) (El-Juhany 2011, Trianoski et al 2011, Duong et al 2017 and medium dimensional stability (Venson et al 2008, Duong andMatsumura 2018a). Mechanical properties of M. azedarach wood were also reported by some researchers (Matsumura et al 2006, Venson et al 2008, Duong and Matsumura 2018b, Duong et al 2019 who suggested the possibility of using wood of M. azedarach as a new timber source. Within-tree variation of M. azedarach physical (Duong and Matsumura 2018a) and mechanical wood properties (Duong and Matsumura 2018b) have also been examined, and it was observed that wood beyond ring 7 from the pith displayed mature wood properties, i.e.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, V s , wood density and ultrasonic velocity which is another non-destructive measurement has also positively related to MOE of some planted hardwood trees (Melia azedarch, Shorea spp. and Maesopsis eminii) [47,48]. Although wood density of the measured trees has not been evaluated in this study, the significant difference of wood density might result in the different V s as shown in such current studies for other species.…”
Section: Discussionmentioning
confidence: 77%